A Critical Analysis of Alternative Dispute Resolution in South Africa and Ghana - Mvikweni, Mlondolozi (Journal of Social Sciences and Humanities, 2026)
This article critically examines the principles, legislative framework, and operational mechanisms of Alternative Dispute Resolution (ADR) in South Africa, drawing comparative insights from Ghana’s consolidated ADR framework under the Alternative Dispute Resolution Act. ADR is increasingly recognized as an essential tool to enhance access to justice, reduce court backlogs, and foster restorative outcomes in civil, criminal, and commercial disputes. The study traces the historical development of ADR in South Africa, evaluating its constitutional and statutory foundations, and analyzing key mechanisms, including arbitration, plea bargaining, and court-annexed mediation. Judicial recognition of ADR in landmark cases such as Telcordia Technologies Inc v Telkom SA Ltd 2007 and Lufuno Mphaphuli & Associates (Pty) Ltd v Andrews reinforces its legitimacy, yet fragmentation across sector-specific statutes limits accessibility, public trust, and uniformity. Ghana’s ADR framework integrates arbitration, mediation, and customary dispute resolution within a single legislative instrument, supported by a national ADR Center, demonstrating a model that could inform South African reform. Using a doctrinal desktop methodology, the study analyses primary legal sources, SALRC reports, and scholarly literature to identify legislative and operational challenges. The study recommends legislative consolidation, professionalization of mediation services, expansion of court-annexed programs, integration of customary dispute resolution, and alignment with international best practices, such as the UNCITRAL Model Law. These reforms could enhance fairness, accessibility, and public confidence, enabling South Africa to realize the constitutional promise of transformative justice.